Results of concurrent HER2 (CERB-B2) staining in the primary tumor and lymph node metastasis in advanced stage gastric carcinoma (Annals of Medical Research, 2021)
Aim: We hypothesized that tumor cells with metastatic capacity and nodal metastasis would exhibit prominent HER2 overexpression in gastric cancer for which intratumoral heterogeneity is highly variable. This study purposed to investigate the mismatch for HER2 immunohistochemical staining between the primary tumor cells and the metastatic cells in patients with advanced-stage gastric cancer.Material and Methods: A hundred and forty-four patients with advanced staged gastric cancer, and lymph node metastasis who underwent surgical resection were enrolled in this retrospective study. Primary tumor and lymph node metastasis underwent concurrent immunohistochemical staining for addressing the HER2 positivity. The concordance of HER2 positivity between the primary tumor samples and the lymph node metastases was investigated.Results: There was a significant difference in HER2 positivity rate among the well, moderate, and poorly differentiated carcinomas, which was primarily driven by the high HER2 overexpression in well-differentiated subgroup. HER2 positivity was highly frequent in stage 3 tumors, whereas HER2 was negative in the majority of the stage 4 tumors. Tumor size was also significantly larger in subjects without HER2 overexpression compared to those with HER overexpression [6 (IQR=4.88) cm vs. 5.25 (IQR=3.5) cm, p = 0.037]. Concordance of primary tumors and the metastatic lymph nodes regarding HER2 positive IHC staining were 93.7%. Conclusion: HER2 might be positive in lymph node metastasis samples even if the primary tumor is negative for HER2. We suggest that HER2 IHC staining of the lymph node metastasis should be considered if the primary tumor is signet ring cell carcinoma, moderately or poorly differentiated, and negative for HER2 in subjects with gastric carcinoma and lymph node metastasis.
Keywords: Gastric carcinoma; HER2 (CerbB2); iymph node; metastasis